Assessing the impact of the economic complexity on the ecological footprint in G7 countries: Fresh evidence under human development and energy innovation processes - Balsalobre-Lorente, Daniel; Nur, Tugba; Topaloglu, Emre E.; Evcimen, Ceren (Elsevier, 2024)
The G-7 economies include economically developed countries on a global scale. The high economic complexity and ecological behaviour of these countries have led to increased concern in other countries within the conjuncture. For this reason, this study investigates the impact of economic complexity, human development, high innovation processes, and renewable energy consumption on the ecological footprint, presenting as the main novelty the damper effect that human development and innovation processes exert on economic complexity and the global effect on the ecological footprint. This empirical evidence is analyzed under the validation of a U -inverted EKC ' s behaviour between ecological footprint and economic complexity for 1991-2018. Our study follows a second -generation perspective that generates reliable and robust results using Cup-FMOLS, Konya panel bootstrap causality and panel VAR analyses under cross-sectional dependence and slope heterogeneity. The long -run elasticity estimates calculated with the Cup-FMOLS approach suggest that economic complexity, human development, high innovation process and interaction variables reduce the ecological footprint. The unidirectional causality from economic complexity and human development to ecological footprint, as well as from economic complexity and human development to the high innovation process, is part of the Konya bootstrap causality test. In addition, a bidirectional causality linkage is revealed between renewable energy consumption and ecological footprint, human development and high innovation process. In G-7 countries, where economic complexity is higher than in other countries, it is crucial to improve environmental quality to ensure sustainable development. The findings show that sustainable development in G-7 countries can be accelerated by improving renewable energy sources, R&D investments and social dimension. (c) 2023 The Author(s). Published by Elsevier B.V. on behalf of International Association for Gondwana Research. This is an open access article under the CC BY -NC -ND license (http://creativecommons.org/ licenses/by-nc-nd/4.0/).
Keywords: Economic complexity; Ecological footprint; Environmental Kuznets curve; Human development; High innovation; Renewable energy; G-7 countries